2012
DOI: 10.1111/j.1747-4949.2012.00794.x
|View full text |Cite
|
Sign up to set email alerts
|

French Adaptation of the Vascular Cognitive Impairment Harmonization Standards: The GRECOG-VASC Study

Abstract: Lower incidence of vascular events following small artery ischemic stroke Small artery infarction, which is particularly prevalent among Asians (1), carries a lower risk of recurrent stroke at one-month compared with other stroke subtypes, but long-term findings are inconsistent (2,3). Data on subsequent myocardial infarction risk after small artery stroke are limited. We compared the incidence of vascular events following ischemic stroke due to small artery disease vs. other etiologies among prospectively rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 5 publications
0
24
0
1
Order By: Relevance
“…The lack of satisfactory criteria for VCI diagnosis and its preventable nature urged the establishment of NINDS-CSN neuropsychological battery [ 7 ]. International effort has been made by validation studies from France [ 9 ], Hong Kong [ 8 ], and Singapore [ 10 ]. Our study was consistent with previous studies, also showing good validity and reliability of the protocols for diagnosing VCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of satisfactory criteria for VCI diagnosis and its preventable nature urged the establishment of NINDS-CSN neuropsychological battery [ 7 ]. International effort has been made by validation studies from France [ 9 ], Hong Kong [ 8 ], and Singapore [ 10 ]. Our study was consistent with previous studies, also showing good validity and reliability of the protocols for diagnosing VCI.…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusion was drawn by researchers in the Singapore [ 10 ] and our previous Hong Kong [ 8 ] validation studies. The French study [ 9 ] (ClinicalTrials.gov ID: NCT01339195) was supposed to end in August 2013, yet no results have been published so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2004; 2007) [32], [33]Groupe de Réflexion pour l'Evaluation COGnitive VASCulaire study (GRECOG-VASC)§France2010–20153606m6 mo6 moVASCOGGodefroy et al. (2012) [34]Helsinki Stroke Aging Memory (SAM)Finland1993–20154863m, 15m, 21y3 moInitialDSMJokinen et al. (2015) [35]; Oksala et al(2009) [36]Maastricht Cognitive Disorders After Stroke (CODAS)Netherlands2000–20031941m, 6m, 1y, 2y1 mo, 6 mo, 1 y, 2 yNoDSM-III, DSM-III-R, DSM-IV, ICD-10, NINDS-AIREN, ADDTCRasquin et al.…”
Section: Methodsmentioning
confidence: 99%
“…Our comparison with the HSP indicated that it does not underestimate the prevalence of cognitive dysexecutive disorder when it is due to arterial infarct or hemorrhage. From a clinical perspective, our study indicates that the assessment of executive functions in stroke should include both a validated inventory of behavioral dysexecutive syndrome and cognitive tests [ 41 ]. In patients with infarct and cerebral hemorrhage, initial assessment may be based on executive function tests from the HSP.…”
Section: Discussionmentioning
confidence: 99%